To Buy or Not to Buy? : Uncertainty, Irreversibility and Heterogeneous Investment Dynamics in Italian Company Data - Lombardi, Domenico (IMF Working Papers; Working Paper ;, 2004)
This study tests for the presence of real options effects induced by uncertainty and (partial) irreversibility on fixed capital investment using Italian company data. The approach recognizes that firm-level investment spending may, itself, be aggregated over multiple investment decisions in separate types of capital goods and emphasizes effects of uncertainty on short-run investment dynamics. Using a survey-based measure of uncertainty related to the assessment of managers responsible for the firms' investment plans, the study finds evidence of heterogeneous and nonlinear dynamics pointing to a slower adjustment of investment in response to demand shocks at higher levels of uncertainty. The results also point to an additional source of nonlinearity originating from a convex response of investment to demand shocks.